2014
DOI: 10.1186/s13018-014-0074-7
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of reamed versus unreamed intramedullary nailing for open tibial fractures

Abstract: BackgroundOpen fractures of the tibial diaphysis are usually caused by high-energy trauma and associated with severe bone and soft tissue injury. Reamed and unreamed intramedullary nailing are often used for treatment of tibial injury. The purpose of this study was to investigate the clinical efficacy of reamed versus unreamed intramedullary nailing for open tibial fractures (OTF).MethodsA meta-analysis was conducted according to the guidelines of the Cochrane Collaboration using databases containing the Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…There is a great discrepancy in infection rate between reamed and unreamed IM nailing when reviewing literature. A recent meta-analysis with the aim of comparing the outcome of these two procedures showed no difference in union rate, secondary surgery rate, implant failure rate, osteofascial compartment syndrome, and infection during the postoperative period (16). Similar to our findings, the risk of infection was similar in both types of procedures (relative risk of 1.03) with an acceptable homogeneity across the analyzed studies.…”
Section: Discussionsupporting
confidence: 88%
“…There is a great discrepancy in infection rate between reamed and unreamed IM nailing when reviewing literature. A recent meta-analysis with the aim of comparing the outcome of these two procedures showed no difference in union rate, secondary surgery rate, implant failure rate, osteofascial compartment syndrome, and infection during the postoperative period (16). Similar to our findings, the risk of infection was similar in both types of procedures (relative risk of 1.03) with an acceptable homogeneity across the analyzed studies.…”
Section: Discussionsupporting
confidence: 88%
“…C remained the best treatment for closed cases in the case of three indices with supportive data. Considering the high risk of bias of trials in included Foote's NMA, and the outcome of some traditional meta-analyses that there was no significant difference between RIN and UIN for open cases, and RIN was recommended by more for closed fractures, we contend our conclusion that the type of fracture was not distinguished (Xue et al, 2010; Li et al, 2013; Shao et al, 2014; Xia et al, 2014; Yu et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“… 53 It has been suggested that reaming allows for the insertion of larger diameter nails and increases stability. 38 , 54 , 55 This may be achieved, however, at the cost of damaging endosteal blood supply and diminishing cortical wall thickness. 56 , 57 Unreamed nailing shows comparable outcomes to reamed nails in terms of infection rates, 38 , 45 , 56 risk of nonunion and rates of re-operation.…”
Section: Principles Of Managementmentioning
confidence: 99%